Bahasa Inggris - Harahap, Faradiba Sari (EDUJ : English Education Journal, 2024)
Songs are among the most widely used forms of media in society to convey ideas and emotions which can draw pragmatics attention. The objective of this research is to analyze the types, and the dominant type of deixis used in song lyrics of “Who I am” by Alan Walker, Putri Ariani and Peder Elias. The researcher elects the song as the object of the analysis because the song is the result of collaboration among three talented singers and one of them is from Indonesia, Putri Ariani. The music video had been watched more than 32 million times and was included in the YouTube Music trending ranks. This research uses qualitative research method. In data collection technique, the researcher uses document analysis. All the types of deixis encompassing personal pronoun, social, discourse, place, and time deictic expressions were found in the song lyrics of “Who I am” by Alan Walker, Putri Ariani and Peder Elias. In person deixis, the deictic expression are personal pronoun. The results of the research indicated (1) there are 99 data of five deixis types found in song lyrics of “Who I am” by Alan Walker, Putri Ariani and Peder Elias, consisting of: 49 data (49.49.7%) of person deixis, 6 data (6.06%) of spatial deixis, 32 data (32.32%) of temporal deixis, 1 word (1.01%) of social deixis, and 11 data (11,11%) of discourse deixis. Thus, the personal deixis (49 deictic words or 49.49%) was the most frequently used deixis.